Lithium battery cell termination adhesive tape and preparation method thereof
Patent Information
- Application Number
- CN202411612494.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant and high temperature resistance of existing lithium battery termination tapes are poor, which poses safety hazards, and may cause deformation during charging and discharging, affecting service life and quality.
Using nano -oxidation microfinance as a functional additive, through ultrasonic dispersing and chemical bonding techniques, modified nano oxide macro balls can make it have excellent high temperature resistance and flame retardant performance in the termination of the tape.
The prepared lithium battery cell termination tape not only has excellent high temperature resistance and flame retardant performance, but also has good anti -deformation performance, effectively ensuring its quality and quality.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery packaging, and in particular to a lithium battery cell termination tape and a preparation method thereof. Background Art
[0002] In recent years, clean energy conversion devices, led by lithium-ion batteries, have developed rapidly. They have the characteristics of high energy storage, large output power and light weight, and are widely used in new energy vehicles and other fields. With the development of national clean energy, household new energy vehicles (BYD, etc.), shared electric scooters (such as Qingju, etc.), and shared pure electric vehicles (such as GoFun Travel, etc.), which are recognized by the public as green and environmentally friendly travel methods, have greatly promoted the development of lithium-ion batteries. In the production of lithium-ion batteries, lithium battery termination tape is needed. It uses PP, PET, and PI film insulation materials as the base material, and is coated with acrylic glue resistant to lithium battery electrolyte on this basis. The thickness is 0.016-0.055 and the colors are green, dark green, blue, transparent, etc. It is specially used for the insulation and fixation of lithium-ion batteries and other parts, and is suitable for the insulation protection and fixation of various lithium-ion battery poles such as cylindrical and square.
[0003] A termination tape for lithium batteries and a preparation method thereof are disclosed in a patent document with application number "CN201811472671.2". The prepared termination tape includes a substrate and glue. The glue includes the following components by weight: 50-100 parts of amino-terminated silicone oil grafted SMA polymer, 30-120 parts of tackifying resin, and 200-750 parts of solvent. Although the termination tape prepared by this patent document has excellent bonding properties, it can improve the safety factor and service life of lithium batteries, and the preparation process is simple and convenient for industrial production. However, its flame retardant properties and high temperature resistance are relatively poor, not only there are certain safety hazards, but also the termination tape may be deformed in the high temperature environment formed by charging and discharging, which affects its service life and quality to a certain extent. Based on this, the present invention provides a lithium battery cell termination tape and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention
[0004] The purpose of the present invention is to provide a lithium battery cell termination tape and a preparation method thereof. The prepared termination tape not only has excellent high temperature resistance and flame retardant properties, but also has good anti-deformation performance, effectively ensuring its quality.
[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a lithium battery cell termination tape, comprising the following steps: Step 1: performing corona treatment on one end surface of the PET substrate to form a rough adhesive surface; Step 2: Apply the release agent on the smooth surface of the PET substrate, then put it into an oven and bake it at 80-90°C for 2-5 minutes to obtain a release layer after curing; Step 3: turn over the PET substrate and evenly apply the adhesive on the upper adhesive surface of the PET substrate at a rate of 12 to 18 m / min, then put it into an oven and bake it at 80 to 90° C. for 2 to 5 minutes to obtain an adhesive layer after curing; finally, after cooling, winding and cutting, a lithium battery cell termination tape is obtained.
[0006] Furthermore, the adhesive is made of the following raw materials in parts by weight: 80 to 100 parts of acrylate monomer, 10 to 15 parts of zinc borate, 4 to 6 parts of melamine octamolybdate, 5 to 8 parts of pentaerythritol, 0.2 to 0.5 parts of azobisisobutyronitrile, 2 to 4 parts of terpene resin, 3 to 5 parts of rosin resin, 10 to 20 parts of N,N-diphenylparaphenylenediamine, 10 to 30 parts of inorganic pigment, 6 to 10 parts of functional additives and 90 to 100 parts of organic solvent.
[0007] Furthermore, the acrylic acid ester monomer is compounded by methyl methacrylate, ethyl acrylate and isobornyl methacrylate in a mass ratio of 1:0.4-0.6:0.5-0.8.
[0008] Furthermore, the terpene resin is selected from any one of hydrogenated terpene resin and polymerized terpene resin; and the softening point of the terpene resin is 100-130°C.
[0009] Furthermore, the inorganic pigment is selected from any one of cobalt green, olive green, cobalt blue and chrome yellow.
[0010] Furthermore, the preparation method of the functional additive comprises the following steps: The first step is to uniformly disperse the nano-cerium oxide microspheres in chloroform at a solid-liquid ratio of 10 to 20 g / L, and then add γ-aminopropyltriethoxysilane in an amount of 0.7 to 1.0 times the mass of the nano-cerium oxide microspheres, and then ultrasonically disperse for 20 to 30 minutes and stir at 80 to 120° C. to react for 20 to 30 hours; Step 2: After the reaction is completed, add triethylamine in an amount of 0.2 to 0.3 times the mass of the nano-cerium oxide microspheres to the resulting component, and then slowly add p-chlorophenylboric acid in an amount of 0.5 to 0.8 times the mass of the nano-cerium oxide microspheres after ultrasonic dispersion for 10 to 15 minutes, stir evenly, and then reflux for 10 to 20 hours, and then react for 30 to 40 hours at room temperature; The third step is to wait for the reaction to be completed, and then the reaction product is allowed to stand, centrifuged and filtered in turn. The filter cake is washed with acetone and anhydrous ethanol for 2 to 3 times, and finally vacuum dried to obtain the functional additive.
[0011] Furthermore, the preparation method of the nano cerium oxide microspheres is as follows: acetic acid and glycol are ultrasonically mixed at a volume ratio of 1:25 to 35 to obtain a mixed component; then an aqueous cerium nitrate solution is added to the mixed component, the mixture is stirred evenly, and the temperature is raised to 155 to 175°C, and the mixture is kept at this temperature for reaction for 3 to 5 hours; after the reaction is completed, the resulting components are centrifuged, and the filter cake is washed and dried and then transferred to a high-temperature calcination device, and calcined at a temperature of 450 to 520°C for 3 to 5 hours; after the calcination is completed, the mixture is naturally cooled to room temperature, and the final product is the nano cerium oxide microspheres.
[0012] Furthermore, the concentration of the cerium nitrate aqueous solution is 0.05-0.1 mol / L, and the dosage ratio of cerium nitrate to mixed components in the cerium nitrate aqueous solution is 1:30-35 g / mL.
[0013] Furthermore, the organic solvent is composed of ethyl acetate and toluene in a mass ratio of 2 to 4:1.
[0014] In a second aspect, the present invention provides a lithium battery cell termination tape, which is prepared by the preparation method described above.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention uses acetic acid, glycol and cerium nitrate aqueous solution as raw materials to prepare nano cerium oxide microspheres with a porous spherical structure. Then the nano cerium oxide microspheres are uniformly dispersed in chloroform, and γ-aminopropyl triethoxysilane is added thereto. After ultrasonic dispersion, the mixture is stirred and heated to react, so that the γ-aminopropyl triethoxysilane is grafted on the surface of the nano cerium oxide microspheres and in their porous structures through chemical bonds, thereby achieving modification of the nano cerium oxide microspheres. Then triethylamine and p-chlorophenylboric acid are added to the resulting components, and finally, under the action of triethylamine, the p-chlorophenylboric acid reacts with the γ-aminopropyl triethoxysilane on the nano cerium oxide microspheres, and finally the p-chlorophenylboric acid is successfully grafted on the surface of the nano cerium oxide microspheres and in their porous structures, thereby preparing a functional additive. The prepared functional additive is composed of nano cerium oxide microspheres and p-chlorophenylboric acid, so that the functional additive has not only excellent high temperature resistance but also excellent flame retardancy. The present invention uses the functional additive as the raw material of the adhesive, so that the prepared termination tape not only has excellent high temperature resistance and flame retardancy, but also has good anti-deformation performance, effectively ensuring its quality. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Example 1 A method for preparing a lithium battery cell termination tape comprises the following steps: Step 1: performing corona treatment on one end surface of the PET substrate to form a rough adhesive surface; Step 2: Apply the release agent on the smooth surface of the PET substrate, then put it into an oven and bake it at 80°C for 2 minutes to obtain a release layer after curing; Step 3: turn over the PET substrate and evenly apply the adhesive on the upper adhesive surface of the PET substrate at a rate of 12 m / min, then put it into an oven and bake it at 80°C for 2 minutes to obtain an adhesive layer after curing; finally, after cooling, winding and cutting, a lithium battery cell termination tape is obtained.
[0018] The adhesive is made of the following raw materials in parts by weight: 80 parts of acrylate monomer, 10 parts of zinc borate, 4 parts of melamine octamolybdate, 5 parts of pentaerythritol, 0.2 parts of azobisisobutyronitrile, 2 parts of terpene resin, 3 parts of rosin resin, 10 parts of N,N-diphenyl-p-phenylenediamine, 10 parts of cobalt green, 6 parts of functional additives and 90 parts of organic solvent; The acrylate monomer is compounded by methyl methacrylate, ethyl acrylate and isobornyl methacrylate in a mass ratio of 1:0.4:0.5; the terpene resin is hydrogenated terpene resin; and the softening point of the terpene resin is 100°C; the organic solvent is composed of ethyl acetate and toluene in a mass ratio of 2:1.
[0019] The preparation method of the functional additive comprises the following steps: The first step is to uniformly disperse the nano-cerium oxide microspheres in chloroform at a solid-liquid ratio of 10 g / L, and then add γ-aminopropyltriethoxysilane with a mass 0.7 times that of the nano-cerium oxide microspheres, and then ultrasonically disperse for 20 minutes and stir at 80°C for 20 hours; Step 2: After the reaction is completed, add triethylamine in an amount 0.2 times the mass of the nano-cerium oxide microspheres to the resulting component, and then slowly add p-chlorophenylboric acid in an amount 0.5 times the mass of the nano-cerium oxide microspheres after ultrasonic dispersion for 10 minutes. After stirring evenly, reflux for 10 hours and then react for 30 hours at room temperature. Step 3: After the reaction is completed, the reaction product is allowed to stand, centrifuged and filtered in sequence. The filter cake is washed twice with acetone and anhydrous ethanol respectively, and finally vacuum dried to obtain the functional additive.
[0020] The preparation method of nano cerium oxide microspheres is as follows: acetic acid and glycol are ultrasonically mixed at a volume ratio of 1:25 to obtain a mixed component; then a cerium nitrate aqueous solution is added to the mixed component, the mixture is stirred evenly, the temperature is raised to 155°C, and the mixture is kept at this temperature for reaction for 3 hours; after the reaction is completed, the obtained product components are centrifuged, and the filter cake is washed and dried and then transferred to a high-temperature calcination device, and calcined at a temperature of 450°C for 3 hours; after the calcination is completed, the mixture is naturally cooled to room temperature, and the final product is the nano cerium oxide microspheres; wherein the concentration of the cerium nitrate aqueous solution is 0.05 mol / L, and the amount ratio of cerium nitrate in the cerium nitrate aqueous solution to the mixed component is 1:30 g / mL.
[0021] Example 2 A method for preparing a lithium battery cell termination tape comprises the following steps: Step 1: performing corona treatment on one end surface of the PET substrate to form a rough adhesive surface; Step 2: Apply the release agent on the smooth surface of the PET substrate, then put it into an oven and bake it at 85°C for 3 minutes to obtain a release layer after curing; Step 3: turn over the PET substrate and evenly apply the adhesive on the upper adhesive surface of the PET substrate at a rate of 15 m / min, then put it into an oven and bake it at 85°C for 3 minutes to obtain the adhesive layer after curing; finally, after cooling, winding and cutting, a lithium battery cell termination tape is obtained.
[0022] The adhesive is made of the following raw materials in parts by weight: 90 parts of acrylate monomer, 12 parts of zinc borate, 5 parts of melamine octamolybdate, 6 parts of pentaerythritol, 0.3 parts of azobisisobutyronitrile, 3 parts of terpene resin, 4 parts of rosin resin, 15 parts of N,N-diphenyl-p-phenylenediamine, 20 parts of olive green, 8 parts of functional additives and 95 parts of organic solvent; The acrylate monomer is compounded by methyl methacrylate, ethyl acrylate and isobornyl methacrylate in a mass ratio of 1:0.5:0.6; the terpene resin is polymerized terpene resin; and the softening point of the terpene resin is 120°C; the organic solvent is composed of ethyl acetate and toluene in a mass ratio of 3:1.
[0023] The preparation method of the functional additive comprises the following steps: The first step is to uniformly disperse the nano-cerium oxide microspheres in chloroform at a solid-liquid ratio of 15 g / L, and then add γ-aminopropyltriethoxysilane with a mass 0.8 times that of the nano-cerium oxide microspheres, and then ultrasonically disperse for 25 minutes and stir at 100° C. for 25 hours; Step 2: After the reaction is completed, add triethylamine in an amount 0.25 times the mass of the nano-cerium oxide microspheres to the resulting component, and then slowly add p-chlorophenylboric acid in an amount 0.6 times the mass of the nano-cerium oxide microspheres after ultrasonic dispersion for 10 minutes. After stirring evenly, reflux for 15 hours and then react for 35 hours at room temperature. The third step is to wait for the reaction to be completed, and then the reaction product is allowed to stand, centrifuged and filtered in turn. The filter cake is washed three times with acetone and anhydrous ethanol respectively, and finally vacuum dried to obtain the functional additive.
[0024] The preparation method of nano cerium oxide microspheres is as follows: acetic acid and glycol are ultrasonically mixed at a volume ratio of 1:30 to obtain a mixed component; then a cerium nitrate aqueous solution is added to the mixed component, the mixture is stirred evenly, the temperature is raised to 165°C, and the mixture is kept at this temperature for reaction for 4 hours; after the reaction is completed, the obtained product components are centrifuged, and the filter cake is washed and dried and then transferred to a high-temperature calcination device, and calcined at a temperature of 500°C for 4 hours; after the calcination is completed, the mixture is naturally cooled to room temperature, and the final product is nano cerium oxide microspheres; wherein the concentration of the cerium nitrate aqueous solution is 0.08 mol / L, and the amount ratio of cerium nitrate in the cerium nitrate aqueous solution to the mixed component is 1:32 g / mL.
[0025] Example 3 A method for preparing a lithium battery cell termination tape comprises the following steps: Step 1: performing corona treatment on one end surface of the PET substrate to form a rough adhesive surface; Step 2: Apply the release agent on the smooth surface of the PET substrate, then put it into an oven and bake it at 90°C for 5 minutes to obtain a release layer after curing; Step 3: turn over the PET substrate and evenly apply the adhesive on the upper adhesive surface of the PET substrate at a rate of 18 m / min, then put it into an oven and bake it at 90°C for 5 minutes to obtain the adhesive layer after curing; finally, after cooling, winding and cutting, the lithium battery cell termination tape is obtained.
[0026] The adhesive is made of the following raw materials in parts by weight: 100 parts of acrylate monomer, 15 parts of zinc borate, 6 parts of melamine octamolybdate, 8 parts of pentaerythritol, 0.5 parts of azobisisobutyronitrile, 4 parts of terpene resin, 5 parts of rosin resin, 20 parts of N,N-diphenyl-p-phenylenediamine, 30 parts of cobalt blue, 10 parts of functional additives and 100 parts of organic solvent; The acrylate monomer is compounded by methyl methacrylate, ethyl acrylate and isobornyl methacrylate in a mass ratio of 1:0.6:0.8; the terpene resin is hydrogenated terpene resin; and the softening point of the terpene resin is 130°C; the organic solvent is composed of ethyl acetate and toluene in a mass ratio of 4:1.
[0027] The preparation method of the functional additive comprises the following steps: The first step is to uniformly disperse the nano-cerium oxide microspheres in chloroform at a solid-liquid ratio of 20 g / L, and then add γ-aminopropyltriethoxysilane in an amount equal to that of the nano-cerium oxide microspheres, and then ultrasonically disperse for 30 minutes and stir at 120° C. to react for 30 hours; Step 2: After the reaction is completed, add triethylamine in an amount 0.3 times the mass of the nano-cerium oxide microspheres to the resulting component, and then slowly add p-chlorophenylboric acid in an amount 0.8 times the mass of the nano-cerium oxide microspheres after ultrasonic dispersion for 15 minutes. After stirring evenly, reflux for 20 hours and then react for 40 hours at room temperature. The third step is to wait for the reaction to be completed, and then the reaction product is allowed to stand, centrifuged and filtered in turn. The filter cake is washed three times with acetone and anhydrous ethanol respectively, and finally vacuum dried to obtain the functional additive.
[0028] The preparation method of nano cerium oxide microspheres is as follows: acetic acid and glycol are ultrasonically mixed at a volume ratio of 1:35 to obtain a mixed component; then a cerium nitrate aqueous solution is added to the mixed component, the mixture is stirred evenly, the temperature is raised to 175°C, and the mixture is kept at this temperature for reaction for 5 hours; after the reaction is completed, the obtained product components are centrifuged, the filter cake is washed and dried, and then transferred to a high-temperature calcination device, and calcined at a temperature of 520°C for 5 hours; after the calcination is completed, the mixture is naturally cooled to room temperature, and the final product is the nano cerium oxide microspheres; wherein the concentration of the cerium nitrate aqueous solution is 0.1 mol / L, and the amount ratio of cerium nitrate in the cerium nitrate aqueous solution to the mixed component is 1:35 g / mL.
[0029] The difference between the comparative example and Example 1 is that an equal amount of nano-cerium oxide microspheres are used to replace the functional additive in this comparative example. Performance test: The relevant performances of the lithium battery cell termination tape samples provided in Examples 1 to 3 and the comparative example were tested respectively, and the test data obtained were recorded in the following table: Test items Flame retardant grade Soak in 50℃ lithium battery electrolyte for 180h Soak in 80℃ lithium battery electrolyte for 48h Example 1 V-0 The adhesive force is 8.9N / 25mm, without falling off, fading or warping The adhesive force is 7.5N / 25mm, without falling off, fading or warping Example 2 V-0 The adhesive force is 9.3N / 25mm, without falling off, fading or warping The adhesive force is 7.6N / 25mm, without falling off, fading or warping Example 3 V-0 The adhesive force is 9.1N / 25mm, without falling off, fading or warping The adhesive force is 7.3N / 25mm, without falling off, fading or warping Comparative Example V-1 The adhesive force is 6.9N / 25mm, the edges are peeling off, the color becomes lighter, and the edges are warped The adhesive force is 4.2N / 25mm, it is almost completely peeled off, the color is seriously lightened, and the curvature is high By comparing and analyzing the relevant data in the table, it can be seen that the termination tape prepared by the present invention not only has excellent high temperature resistance and flame retardancy, but also has good anti-deformation performance, which effectively guarantees its quality. This shows that the lithium battery cell termination tape and preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.
[0030] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0031] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a lithium battery cell termination tape, characterized in that: The following steps are involved: Step 1: performing corona treatment on one end surface of the PET substrate to form a rough adhesive surface; Step 2: Apply the release agent on the smooth surface of the PET substrate, then put it into an oven and bake it at 80-90°C for 2-5 minutes to obtain a release layer after curing; Step 3: turn over the PET substrate and evenly apply the adhesive on the upper adhesive surface of the PET substrate at a rate of 12 to 18 m / min, then put it into an oven and bake it at 80 to 90° C. for 2 to 5 minutes to obtain an adhesive layer after curing; finally, after cooling, winding and cutting, a lithium battery cell termination tape is obtained.
2. A lithium battery cell termination tape according to claim 1, characterized in that: The adhesive is prepared from the following raw materials in parts by weight: 80 to 100 parts of acrylate monomers, 10 to 15 parts of zinc borate, 4 to 6 parts of melamine octamolybdate, 5 to 8 parts of pentaerythritol, 0.2 to 0.5 parts of azobisisobutyronitrile, 2 to 4 parts of terpene resin, 3 to 5 parts of rosin resin, 10 to 20 parts of N,N-diphenyl-p-phenylenediamine, 10 to 30 parts of inorganic pigments, 6 to 10 parts of functional additives and 90 to 100 parts of organic solvents.
3. A lithium battery cell termination tape according to claim 2, characterized in that: The acrylic acid ester monomer is prepared by compounding methyl methacrylate, ethyl acrylate and isobornyl methacrylate in a mass ratio of 1:0.4-0.6:0.5-0.
8.
4. A lithium battery cell termination tape according to claim 2, characterized in that: The terpene resin is selected from any one of hydrogenated terpene resin and polymerized terpene resin; and the softening point of the terpene resin is 100-130°C.
5. A lithium battery cell termination tape according to claim 2, characterized in that: The inorganic pigment is selected from any one of cobalt green, olive green, cobalt blue and chrome yellow.
6. A lithium battery cell termination tape according to claim 2, characterized in that: The preparation method of the functional additive comprises the following steps: The first step is to uniformly disperse the nano-cerium oxide microspheres in chloroform at a solid-liquid ratio of 10 to 20 g / L, and then add γ-aminopropyltriethoxysilane in an amount of 0.7 to 1.0 times the mass of the nano-cerium oxide microspheres, and then ultrasonically disperse for 20 to 30 minutes and stir at 80 to 120° C. to react for 20 to 30 hours; Step 2: After the reaction is completed, add triethylamine in an amount of 0.2 to 0.3 times the mass of the nano-cerium oxide microspheres to the resulting component, and then slowly add p-chlorophenylboric acid in an amount of 0.5 to 0.8 times the mass of the nano-cerium oxide microspheres after ultrasonic dispersion for 10 to 15 minutes, stir evenly, and then reflux for 10 to 20 hours, and then react for 30 to 40 hours at room temperature; The third step is to wait for the reaction to be completed, and then the reaction product is allowed to stand, centrifuged and filtered in turn. The filter cake is washed with acetone and anhydrous ethanol for 2 to 3 times, and finally vacuum dried to obtain the functional additive.
7. A lithium battery cell termination tape according to claim 6, characterized in that: The preparation method of the nano cerium oxide microspheres is as follows: acetic acid and glycol are ultrasonically mixed uniformly at a volume ratio of 1:25-35 to obtain a mixed component; then a cerium nitrate aqueous solution is added to the mixed component, the mixture is mixed and stirred uniformly, the temperature is raised to 155-175°C, and the mixture is kept at this temperature for reaction for 3-5 hours; after the reaction is completed, the obtained product components are centrifuged, the filter cake is washed and dried, and then transferred to a high-temperature calcination device, and calcined at a temperature of 450-520°C for 3-5 hours; after the calcination is completed, the mixture is naturally cooled to room temperature, and the final product is the nano cerium oxide microspheres.
8. A lithium battery cell termination tape according to claim 7, characterized in that: The concentration of the cerium nitrate aqueous solution is 0.05-0.1 mol / L, and the dosage ratio of the cerium nitrate to the mixed components in the cerium nitrate aqueous solution is 1:30-35 g / mL.
9. A lithium battery cell termination tape according to claim 2, characterized in that: The organic solvent is composed of ethyl acetate and toluene in a mass ratio of 2 to 4:
1.
10. A lithium battery cell termination tape, characterized in that: The lithium battery cell termination tape is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Terminating adhesive tape for lithium battery and preparation method of terminating adhesive tape
CN109593485A